BIAYA PRODUKSI PENEBANGAN DAN PENYARADAN KAYU JATI (Tectona Grandis L.f) UNGGUL NUSANTARA DI KEBUN PERCOBAAN UNIVERSITAS NUSA BANGSA - Jenaro, Azwan Valdes; Lidiawati, Ina; Rusli, Abdul Rahman (Universitas Nusa Bangsa, 2018)
Timber harvesting in Jati Unggul Nusantara (JUN) plantation forest at the Nusa Bangsa University Garden has entered the age of ripening, therefore the harvesting is already necessary. The cost of harvesting JUN production is still currently not available, especially for the costs of logging, skidding, and stump cleaning. The cost of these are very much needed as to determine the business feasibility of the JUN. The aims of this study are to calculate the cost of producing logging, skidding and stump cleaning of JUN arrears in the Cogreg experimental garden of Nusa Bangsa University. The method used is a field observation method, as it’s to describe and explain the production activities. The quantitative approach is the approach that taken by record and analyze the research data. The result shows that the average production cost of logging was Rp. 92,406.91 / m3, while the extraction costs Rp. 130,000.42 / m3, and production costs for arrears cleaning Rp. 80,002.31. So that the total production cost of logging, skidding, and cleaning of arrears are Rp. 30,409.64 / m3.